2007
DOI: 10.3766/jaaa.18.7.5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Event-Related Brain Potentials in Assessing Central Auditory Processing

Abstract: The perception of complex acoustic signals such as speech and music depends on the interaction between peripheral and central auditory processing. As information travels from the cochlea to primary and associative auditory cortices, the incoming sound is subjected to increasingly more detailed and refined analysis. These various levels of analyses are thought to include low-level automatic processes that detect, discriminate and group sounds that are similar in physical attributes such as frequency, intensity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 99 publications
1
43
0
1
Order By: Relevance
“…P1-N1-P2 • To screen participants for the physiological detection of the auditory stimuli, the P1-N1-P2 complex of each deviant stimulus was examined when that stimulus was presented alone in a single block. These components are classified as "obligatory" because they reflect the physiological detection of audible stimulus energy and occur before discrimination of acoustic features (Alain & Tremblay 2007). Like the MMN and P3a, this complex may be elicited without the participant's attention to the stimuli (Bertoli et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P1-N1-P2 • To screen participants for the physiological detection of the auditory stimuli, the P1-N1-P2 complex of each deviant stimulus was examined when that stimulus was presented alone in a single block. These components are classified as "obligatory" because they reflect the physiological detection of audible stimulus energy and occur before discrimination of acoustic features (Alain & Tremblay 2007). Like the MMN and P3a, this complex may be elicited without the participant's attention to the stimuli (Bertoli et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…These components are part of an automatic sensory system that detects and discriminates acoustic parameters such as frequency, intensity, duration, and sound location (Berti et al 2004;Alain & Tremblay 2007). P1 was intended to be used as a screening measure for the physiological detection of the auditory stimuli; however, significant group differences were felt to be relevant to this article, and further analysis was completed.…”
Section: Preattentional Caepsmentioning
confidence: 99%
“…Several researchers have shown that short-term auditory training can be effective in developing perceptual changes. In particular, auditory training paradigms designed to adapt to the individual's performance were successful in demonstrating desired training effects (Alain and Tremblay, 2007;Fu and Galvin, 2007;Sullivan et al, 2013;Tremblay, 2007). The present study extends these techniques to determine whether listeners attending to CI simulations can be trained to focus on voice gender cues in the challenging situation where competing talkers are present.…”
Section: Introductionmentioning
confidence: 70%
“…The auditory training paradigm was designed to adapt to the individual's performance across several levels. This type of perceptual training has been successful in examining neural and behavioral changes in animals and humans (Alain and Tremblay, 2007;Atienza et al, 2002;Boothroyd, 2010;Kilgard et al, 2007;Moucha and Kilgard, 2006;Tremblay et al, 1997;Tremblay et al, 1998). Auditory training in noise resulted in improved speech recognition in noise for adults with HI and in some instances led to a generalization of improvements to novel stimuli (Burk and Humes, 2008;Sweetow and Sabes, 2006).…”
Section: Introductionmentioning
confidence: 93%